Perfil clínico microbiológico de pacientes Neutropênicos Febris em tratamento oncológico na unidade de internação pediátrica do Hospital das Clínicas da UFMG - Mariana Antunes Faria Lima (2019)
ABSTRACT Background: Infection is major problem for children with onco-hematological diseases. Our aim was to identify factors associated with documented infection, in children with febrile neutropenia and cancer. Methods: We conducted a prospective, population-based cohort study that included children ≤18 years of age with onco-hematological diseases and febrile neutropenia between June 2016 and June 2018 treated at a reference center. Definition of documented infection was based on CDC criteria. Patients with hematopoietic stem cell transplantation were excluded. Results: 172 episodesof febrile neutropenia were included. Median age was 7.3 (IQR) 4.0-10.0) years and 69 (32,7%) had LLA. Factors identiﬁed in univariate analysis were female sex, monocytes count <100cells/mm³, platelets <50,000, reactive C protein > 90 mg/dl, hemoglobin level <7g/dL, second episode of febrile neutropenia or more, first fever at hospital and positive first blood culture. In multivariate analysis the variables that remained as independent predictive risk ³, platelets > 50,000 (0,43 OR, IC95% 0,21; 0,88 p 0,021), reactive C protein > 90 mg/dl (3,18 OR, IC95% 1,32; 7,68 p 0,01), first episode of febrile neutropenia (0,34 OR, IC95% 0,13; 0,92 p 0,034), first fever at hospital (5,88 OR, IC95% 2,75; 12,57 <p 0,001) and positive first blood culture (3,71 OR, IC95% 1,18; 11,61 p 0,025). Conclusions: This study found risk fators for infection in patients with febrile neutrpenia using clinical and laboratorial parameters accessible in medical practice. Key words: “Risk,” “Bacteremia”, “Febrile Neutropenia” and “Child”